2014
DOI: 10.18632/oncotarget.2348
|View full text |Cite
|
Sign up to set email alerts
|

AP4 is required for mitogen- and c-MYC-induced cell cycle progression

Abstract: AP4 represents a c-MYC-inducible bHLH-LZ transcription factor, which displays elevated expression in many types of tumors. We found that serum-starved AP4-deficient mouse embryo fibroblasts (MEFs) were unable to resume proliferation and showed a delayed S-phase entry after restimulation. Furthermore, they accumulated as tetraploid cells due to a cytokinesis defect. In addition, AP4 was required for c-MYC-induced cell cycle re-entry. AP4-deficient MEFs displayed decreased expression of CDK2 (cyclin-dependent ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 37 publications
3
21
0
Order By: Relevance
“…Elevated expression of AP4 is associated with an increased metastatic capacity in colorectal cancer (6) and AP4 predicts poor prognosis in non-small cell lung cancer (25). In addition, several studies have demonstrated the critical role of AP4 in cancers and in immunology (26)(27)(28). Therefore, this study contributes to our understanding of cancer biology.…”
Section: Discussionmentioning
confidence: 70%
“…Elevated expression of AP4 is associated with an increased metastatic capacity in colorectal cancer (6) and AP4 predicts poor prognosis in non-small cell lung cancer (25). In addition, several studies have demonstrated the critical role of AP4 in cancers and in immunology (26)(27)(28). Therefore, this study contributes to our understanding of cancer biology.…”
Section: Discussionmentioning
confidence: 70%
“…The human transcription factor activating protein-4 (AP4) is a basic helix-loop-helix leucine-zipper (bHLH-LZ) transcription factor, which forms homodimers that bind to the Ebox motif CAGCTG [10][11][12][13][14][15]. AP4 has been found to be a direct transcriptional target of c-MYC.…”
Section: Introductionmentioning
confidence: 99%
“…Upon activation, AP4 targets p21 to antagonize cell cycle arrest [15][16][17]. AP4 expression is upregulated in some cancers, e.g., breast cancer, colorectal carcinoma, and hepatocellular carcinoma [10][11][12][13][14][15]. In addition, an increase in the levels of AP4 has been reported in NSCLC, in which AP4 was found to augment epithelialmesenchymal transition (EMT) to increase NSCLC cell invasiveness [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…AP4 was discovered to bind to the enhancer of the SV40 viral genome and activate its late transcription in vitro [49], and it attracts an increasing amount of attention because of its broad range of functions in regulating cell proliferation [13,14,17], death [15], development [18], and aging [16]. In this study, we determined that the long-term overexpression of AP4 in RPE cells ARC induced cell enlargement and flattening accompanied by cessation of cell proliferation.…”
Section: Discussionmentioning
confidence: 89%
“…Many target genes of AP4, such as insulin-like growth factor binding protein-2, caspase 9, p21, and Pin1, have recently been identified [13][14][15][16]. On the basis of the increasing number of target genes of AP4 discovered, AP4 seems to participate in several crucial physiological activities in mammalian cells, including cell proliferation [13,14,17], death [15], development [18], and aging [16]. The Hermeking group demonstrated that ectopic activation of c-MYC leads to an increase in AP4 in MCF-7 cells and determined that the AP4 gene is a direct transcriptional target of c-MYC [14].…”
Section: Introductionmentioning
confidence: 99%